2023
DOI: 10.1002/1873-3468.14698
|View full text |Cite
|
Sign up to set email alerts
|

Host–microbiome interactions in nicotinamide mononucleotide (NMN) deamidation

Abstract: The nicotinamide adenine dinucleotide (NAD+) precursor nicotinamide mononucleotide (NMN) is a proposed therapy for age‐related disease, whereby it is assumed that NMN is incorporated into NAD+ through the canonical recycling pathway. During oral delivery, NMN is exposed to the gut microbiome, which could modify the NAD+ metabolome through enzyme activities not present in the mammalian host. We show that orally delivered NMN can undergo deamidation and incorporation in mammalian tissue via the de novo pathway, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 80 publications
(192 reference statements)
1
12
0
Order By: Relevance
“…However, Grozio et al defended their work, providing evidence supporting their optimized analytical methods [21,45]. Furthermore, tracer studies on NMN metabolism yield inconsistent results as some suggest significant NMN conversion to NR in the gut, with limited direct absorption [40,46]. In contrast, another study detected NMN in the intestine within 10 minutes of oral intake, supporting the role of Slc12a8 in direct transport [33].…”
Section: Uptake Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Grozio et al defended their work, providing evidence supporting their optimized analytical methods [21,45]. Furthermore, tracer studies on NMN metabolism yield inconsistent results as some suggest significant NMN conversion to NR in the gut, with limited direct absorption [40,46]. In contrast, another study detected NMN in the intestine within 10 minutes of oral intake, supporting the role of Slc12a8 in direct transport [33].…”
Section: Uptake Mechanismsmentioning
confidence: 99%
“…A major challenge for oral NMN supplementation is its extensive first-pass metabolism in the liver. Studies across various dosages (50 mg/kg to 500 mg/kg) consistently show that nearly all ingested NMN is converted into NAM within the liver [29,40,46]. This minimizes the amount of intact NMN available for direct NAD+ synthesis in the liver and prevents it from reaching peripheral tissues, significantly impacting overall bioavailability.…”
Section: Hepatic First-pass Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This microbial deamidation process was important for NAD+ synthesis in the colon, liver, and kidney. Similarly, another study showed that gut bacteria facilitated the deamidation of orally administered NMN, yielding the metabolites NAR and NAMN (in the gut and liver), and NAAD (in the liver) for incorporation into NAD+ via the de novo pathway [ 40 ]. In germ-free mice, NMN escaped microbial deamidation and instead fueled the salvage pathway, leading to elevated levels of amidated metabolites, NR and NMN.…”
Section: Impact Of Metabolism On Supplementationmentioning
confidence: 99%
“…However, a key difference in the time of sampling (minutes vs. hours) indicated both routes of uptake are feasible. Tracer studies on NMN metabolism also yield inconsistent results, as some suggest significant NMN conversion to NR in the gut, with limited direct absorption [ 40 , 46 ]. In contrast, a study detected NMN in the intestine within 10 min of oral intake, supporting the role of Slc12a8 in direct transport [ 33 ].…”
Section: Impact Of Metabolism On Supplementationmentioning
confidence: 99%